Architecture (and the other 99%): Open‐Source Architecture and Design Commons. (November 2013) - Parvin, Alastair; Mosley, Jonathan; Sara, Rachel
Abstract Under the current commercial practice model, can architecture ever really be cutting‐edge or egalitarian in its aims? If only 2 per cent of the world's buildings are designed by architects for 1 per cent of the richest clients, is it possible to design for a wide cross section of the population let alone be truly subversive? Alastair Parvin of architecture studio 00 (zero zero) and co‐founder of the Wiki‐House puts the case forward for a whole new model of open‐source practice.